Aluminomagnesium hydrogel as an efficient and reusable dye scavenger - Rozita M Moattari; Mostafa Mahinroosta; Seyed Nezameddin Ashrafizadeh (Materials Letters: X, 2022)
In the present research work, an aluminomagnesium hydrogel was synthesized via co-precipitation, organic solvent-based aging, and microwave irradiation drying. The synthesized hydrogel was used to remove methylene blue dye from aqueous solutions. The adsorption experiments at room temperature indicated a removal efficiency of 99.7% under an adsorbent dosage of 4 g/L and a duration of 30 min. The adsorbent regeneration tests also confirmed the reusability of the adsorbent for the removal of dye, so that after five regeneration cycles, the hydrogel exhibited a removal efficiency of more than 90% under the same conditions. Overall, the results confirmed that the synthesized aluminomagnesium hydrogel could be used as a promising dye scavenger for methylene blue.